2013
DOI: 10.1002/ana.23884
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine from edible Solanaceae and risk of Parkinson disease

Abstract: Objective To test whether risk of Parkinson disease (PD) is associated with consumption of nicotine-containing edibles from the same botanical family as tobacco, Solanaceae, including peppers, tomatoes and potatoes. Methods In a population-based study with 490 newly diagnosed idiopathic PD cases diagnosed during 1992–2008 at the University of Washington Neurology Clinic or Group Health Cooperative in western Washington State and 644 unrelated, neurologically normal controls, we examined whether PD was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…While a theory to explain these results is lacking, they are consistent with the findings of an older study [40]. Similarly, the results for caffeine intake [9] [13] [31] and nicotine intake [33] are similar to those reported by previous literature [41]- [45]. Whether this will develop into a warrant for a recommendation that people consume only black coffee, and to do so a specific number of times per day remains to be seen.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While a theory to explain these results is lacking, they are consistent with the findings of an older study [40]. Similarly, the results for caffeine intake [9] [13] [31] and nicotine intake [33] are similar to those reported by previous literature [41]- [45]. Whether this will develop into a warrant for a recommendation that people consume only black coffee, and to do so a specific number of times per day remains to be seen.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to these population-based epidemiologic studies, three large case-control studies were also examined [31]- [33]. Tanaka et al [31] assessed the association of the intake of coffee, other caffeine containing beverages, and caffeine with the risk of PD in Japan, in a case-control study including 249 PD cases and 368 control subjects.…”
Section: A Gaba 201mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, attenuation of oxidative damage by natural constituents has been considered as an attractive complementary proposition to delay or prevent the development/progression of several NDD including PD. Epidemiological and biochemical studies have recently identified promising components in certain food groups that may elicit neuroprotection in PD [7]. Interestingly, few recent studies have also indicated an increasing risk of malnutrition among PD patients and that malnourished patients remain under-recognized by health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that nutrition may play an important role in PD. Epidemiological and biochemical studies have recently identified promising components in certain food groups that may elicit neuroprotection in PD (Searles Nielsen et al, 2013;Shaltiel-Karyo et al, 2013). However, inclusion or exclusion of other food groups may trigger or exacerbate neurodegeneration.…”
mentioning
confidence: 99%